2009
DOI: 10.1177/014556130908800210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sequential Dermatophagoides Pteronyssinus Antigen Stimulation on Anatomy and Physiology of the Larynx

Abstract: The goal of this investigation was to study the effects of sequential dust mite antigen stimulation on the appearanceandfunction ofthelarynx. To that end,wedesigned a randomized, placebo-controlled, double-blind, prospective analysis of adults who had tested positive for perennial dust mite allergy. The larynx ofpatients who received the active antigen waschallenged directly with a low (1:100) and a high (1:40) concentration of the dust mite allergen via an oral nebulizer. Voice laboratory assessment tools inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Allergic disease is not limited to the nasal passages, and the concept of the unified airway suggests that inflammation in one area can affect other areas of the aerodigestive tract as well, including the lower airways . Increasing evidence is mounting that laryngeal and vocal symptoms can be attributable to allergic laryngitis, and that introduction of allergens into the larynx can result in vocal fold edema, an increase in laryngeal symptoms, resulting in increases in the subglottic pressure needed to phonate . Laryngeal symptoms that have been attributed to allergic disease are nonspecific and include hoarseness, cough, throat clearing, globus sensation, excessive mucous, and sore throat or throat discomfort .…”
Section: Introductionmentioning
confidence: 99%
“…Allergic disease is not limited to the nasal passages, and the concept of the unified airway suggests that inflammation in one area can affect other areas of the aerodigestive tract as well, including the lower airways . Increasing evidence is mounting that laryngeal and vocal symptoms can be attributable to allergic laryngitis, and that introduction of allergens into the larynx can result in vocal fold edema, an increase in laryngeal symptoms, resulting in increases in the subglottic pressure needed to phonate . Laryngeal symptoms that have been attributed to allergic disease are nonspecific and include hoarseness, cough, throat clearing, globus sensation, excessive mucous, and sore throat or throat discomfort .…”
Section: Introductionmentioning
confidence: 99%
“…b-e Videostroboscopic laryngeal images of an allergic singer at diVerent time points in relation to provocation and during the pollen season: at baseline (b), 1 h after grass pollen provocation (c), 24 h after grass pollen provocation (d), during the pollen season (e) study of Reidy et al [11], where no diVerence in laryngostroboscopic assessment was found before and at 30 min after nasal provocation with house dust mite allergen. In contrast to these Wndings, Dworkin et al [12] observed in their study an induction of endolaryngeal secretions and vocal fold edema after provocation with the highest concentration of allergen (1/40). In our study, a nasal provocation with grass pollen allergen in high concentrations (minimum 1/10) was performed and all allergic subjects had a reduction in PNIF and induction of nasal complaints after provocation.…”
Section: Discussionmentioning
confidence: 64%
“…Here, no diVerence in subjective and objective voice assessment was found after 30 min. The same group recently described an experiment using high-dose house dust mite allergen (concentration 1/40) [12]. Endolaryngeal secretions and vocal fold edema were described on videolaryngostroboscopy after provocation with the higher concentration, while no eVect was seen after provocation with a lower concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Randhawa et al found that patients with a greater number of allergies had worse subjective report of dysphonia . These studies and others begin to establish a link between the environment and laryngitis …”
Section: Discussionmentioning
confidence: 82%
“…Leonard et al (1995) identified histologic evidence of CL in bonnet monkeys exposed to daily ozone for 3 months . Translating this work to humans, Dworkin et al induced laryngitis in individuals exposed to HDMA and Naito et al found that individuals with allergy and pollution exposure had more throat symptoms than patients with only allergies . Similarly, Randhawa et al found that patients with a greater number of allergies had worse subjective report of dysphonia .…”
Section: Discussionmentioning
confidence: 99%